Evaluation of the Impact of Low Emission Zone and Heavy Traffic Ban in Munich (Germany) on the Reduction of PM10 in Ambient Air - Veronika Fensterer (International Journal of Environmental Research and Public Health, 2014)
Concentrations of ambient fine particles (PM10: particles with an aerodynamic diameter ≤ 10 µm) are still exceeding current air quality standards in many European cities. In Munich (Germany), low emission zone and transit bans for heavy-duty vehicles were introduced in 2008 aiming at reduction of traffic emissions contribution to PM10. The effects of those measures on PM10 mass concentrations in Munich were investigated with a semiparametric regression model for modeling PM10 levels adjusted for time, background pollution, public holidays and wind direction. The reduction of PM10 concentration after the introduction of the measures was larger at a traffic monitoring site (13.0 %, 19.6 % in summer, and 6.8 % in winter) and smaller in urban background (4.5 %, 5.7 % in summer, and 3.2 % in winter). The effect was most pronounced on Fridays and on the weekends in summer.